2020
DOI: 10.3390/molecules26010074
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Phytoremediation and Phytoexcretion of NTO from Industrial Wastewater by Vetiver Grass

Abstract: The use of insensitive munitions such as 3-nitro-1,2,4-triazol-5-one (NTO) is rapidly increasing and is expected to replace conventional munitions in the near future. Various NTO treatment technologies are being developed for the treatment of wastewater from industrial munition facilities. This is the first study to explore the potential phytoremediation of industrial NTO-wastewater using vetiver grass (Chrysopogon zizanioides L.). Here, we present evidence that vetiver can effectively remove NTO from wastewat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…It is reported that vetiver grass can effectively treat contaminants, such as organic matter, nutrients, heavy metals, as well as aromatic mixtures that are highly tolerant against extreme weather conditions (cold, hot, flood, and water shortage). According to the reports, vetiver has the capability of remediating toxic heavy-metal-polluted soil and water [92], herbicides [93], petroleum hydrocarbons (PHCs) [94], nuclear waste [95], acid mine drainage [96], textile dyes [97], ciprofloxacin (CIP), and tetracycline (TTC) [98], as well as 3-nitro-1,2,4-triazol-5-one (NTO) [99]. According to the unique characteristics reported for vetiver grass in the previous sections, several recent studies used this plant species to remove or decrease pollutants in unconventional water.…”
Section: Vetiver System To Reduce/eliminate Contaminants From Unconve...mentioning
confidence: 99%
“…It is reported that vetiver grass can effectively treat contaminants, such as organic matter, nutrients, heavy metals, as well as aromatic mixtures that are highly tolerant against extreme weather conditions (cold, hot, flood, and water shortage). According to the reports, vetiver has the capability of remediating toxic heavy-metal-polluted soil and water [92], herbicides [93], petroleum hydrocarbons (PHCs) [94], nuclear waste [95], acid mine drainage [96], textile dyes [97], ciprofloxacin (CIP), and tetracycline (TTC) [98], as well as 3-nitro-1,2,4-triazol-5-one (NTO) [99]. According to the unique characteristics reported for vetiver grass in the previous sections, several recent studies used this plant species to remove or decrease pollutants in unconventional water.…”
Section: Vetiver System To Reduce/eliminate Contaminants From Unconve...mentioning
confidence: 99%
“…is is the first study to discover the potential plant treatment of industrial NTO wastewater using Vetiver grass (Chrysopogon zizanioides L.). e results showed that vetiver can effectively remove NTO from wastewater and also transfer NTO from the root to the stem [32,33].…”
Section: Introductionmentioning
confidence: 97%